The Mackenzie Delta: An archetypal permafrost landscape - Burn, C. (Christopher R.) (2010)
The Mackenzie Delta, in Canada's western Arctic, is North America's largest arctic delta. For over half the year the rivers and lakes of this vast alluvial plain are ice covered. Permafrost is ubiquitous in the delta and the surrounding landscape. Treeline traverses the delta, separating closed-canopy white spruce forests in southern parts from low shrub tundra and sedge wetlands at the Beaufort Sea coast. The extension of the delta northwards into the ocean is the net result of 128 Mt of sediment brought annually to the delta by Mackenzie and Peel Rivers, of which about two thirds are deposited offshore. The permafrost of the uplands adjacent to the delta is ice-rich, with numerous tabular bodies of almost pure ice that formed when the ground originally froze. Throughout the region the terrain surface is criss-crossed by networks of ice-wedge polygons, formed by water freezing in cracks opened by ground contraction during winter cooling. The world's largest population of pingos - ice-cored, conical hills up to 50 m high - has developed in the sandy sediments of drained lakes in the area. These features form as permafrost aggrades in saturated lake sediments, and continual uplift of these little hills demonstrates the enormous forces that can be generated by ground freezing.